PENERAPAN MODEL PEMBELAJARAN BERPIKIR INDUKTIF DI SEKOLAH DASAR - Zulvitri (Jurnal Komunikasi, 2026)
Elementary school learning plays a crucial role in developing students' thinking skills, particularly critical thinking skills, which are crucial for facing the challenges of the 21st century. One learning approach that can be used to develop these skills is the inductive thinking model. This model emphasizes a learning process that begins with the observation of specific facts and progresses to the formation of more general concepts or generalizations. This model actively engages students in the thinking process, rather than passively receiving information from the teacher. This study aims to examine the implementation of the inductive thinking model in elementary schools, identify its advantages and disadvantages, and analyze its impact on students' critical thinking skills. The method used in this study was library research, which involved reviewing various literature in the form of books, scientific journals, and previous research findings relevant to the topic. The data obtained were then analyzed descriptively and qualitatively to gain a comprehensive understanding of the application of this learning model. The results of the study indicate that the inductive thinking model has several advantages, including increasing student engagement in learning, fostering analytical and reasoning skills, and helping students understand concepts more deeply. Furthermore, this model is also effective in developing critical thinking skills because students are trained to observe, classify, compare, and draw conclusions independently. In this process, students not only memorize material but also understand the meaning behind the concepts they learn. However, implementing the inductive thinking learning model also has several drawbacks. This model requires relatively more time than conventional methods, making it less effective when used in limited learning environments. Furthermore, teachers are required to have advanced skills in designing learning and guiding students to ensure the induction process runs smoothly. Not all students have the same initial thinking abilities, so additional strategies are needed to ensure all students can participate optimally in learning. The impact of implementing the inductive thinking learning model on students' critical thinking skills is quite significant. Students become more accustomed to identifying problems, collecting data, analyzing information, and developing arguments based on available evidence. This indicates that the inductive thinking learning model can be an effective alternative for improving the quality of learning in elementary schools. Based on the results of this study, it can be concluded that the inductive thinking learning model has significant potential for improving the critical thinking skills of elementary school students. Therefore, teachers are advised to integrate this model into the learning process while still considering student conditions and existing limitations. School support and teacher competency development are also important factors in the successful implementation of this model.